Meropenem–Vaborbactam Pharmacokinetic-Pharmacodynamic (PK-PD) Target Attainment Analyses as Support for Dose Selection in Patients with Normal Renal Function and Varying Degrees of Renal Impairment. (4th October 2017) - Bhavnani, Sujata M; Trang, Michael; Griffith, David C; Lomovskaya, Olga; Hammel, Jeffrey P; Loutit, Jeffrey S; Dudley, Michael N; Ambrose, Paul G; Rubino, Christopher M
Abstract: Background: Meropenem-vaborbactam is a broad-spectrum carbapenem-β-lactamase inhibitor combination that is being developed to treat patients with serious gram-negative infections, including those caused by Klebsiella pneumoniae carbapenemase (KPC)-producing Enterobacteriaceae (ENT). PK-PD target attainment analyses were undertaken using Monte Carlo simulation, population PK models, non-clinical PK-PD targets for efficacy, and in vitro surveillance data to provide meropenem-vaborbactam dose selection. Methods: Four simulated patient populations ( n = 1000 each) varying by creatinine clearance (CLcr) were generated. Using meropenem and vaborbactam population PK models [Trang M et al . Microbe 2017, P2118], individual post-hoc parameter estimates were generated. Using these estimates, total-drug concentration-time profiles were generated for simulated patients with CLcr of ≥40–150 mL/minute, ≥20 to 40 mL/minute, ≥10 to 20 mL/minute, and ≥0 to 10 mL/minute who received meropenem-vaborbactam 2 g – 2 g q8h, 1 g – 1 g q8h, 1 g – 1 g q12h, 500 mg–500 mg q12h, respectively, as a 3-hour infusion. Using protein binding estimates (2 and 33%, respectively), Day 1 free-drug meropenem %T>MIC and vaborbactam AUC:MIC ratio were calculated. Percent probabilities of achieving meropenem %T>MIC targets of 30, 35 and 45% associated with net bacterial stasis, and 1- and 2-log10 CFU reductions from baseline, respectively, and the ratio of vaborbactam AUC to meropenem-vaborbactam MIC associated with net bacterial stasis were evaluated. An algorithm to assess PK-PD target attainment at meropenem and corresponding meropenem-vaborbactam MIC values based on in vitro surveillance data for ENT and KPC-producing ENT was followed. For P. aeruginosa, meropenem %T>MIC targets alone were assessed relative to meropenem-vaborbactam MIC values. Results: Figures 1 to 3 show high percent probabilities of PK-PD target attainment at or above the upper margins of meropenem-vaborbactam MIC distributions for ENT, KPC-producing ENT, P. aeruginosa were observed across all renal function groups. Conclusion: These data provide support for meropenem 2 g–vaborbactam 2 g q8h administered as a 3-hour infusion and adjusted dosage regimens for patients with varying degrees of renal impairment. Disclosures: S. M. Bhavnani, The Medicines Company: Research Contractor, Research support; M. Trang, The Medicine's Company: Research Contractor, Research support; D. C. Griffith, The Medicine's Company: Employee and Shareholder, Salary; O. Lomovskaya, The Medicine's Company: Employee and Shareholder, Salary; J. P. Hammel, The Medicine's Company: Research Contractor, Research support; J. S. Loutit, The Medicine's Company: Employee and Shareholder, Salary; M. N. Dudley, The Medicine's Company: Employee and Shareholder, Salary; P. G. Ambrose, The Medicine's Company: Research Contractor, Research support; C. M. Rubino, The Medicine's Company: Research Contractor, Research support.